Workshop Measuring Training to improve the Basic Engineering Competence of LPK. Bintang Manufaktur Tegal Indonesia students: Diklat Measuring untuk meningkatkan Kompetensi Basic Engineering Siswa LPK. Bintang Manufaktur Tegal Indonesia - Syarifudin, Syarifudin; Fatkhurrozak, Faqih; Sanjaya, Firman Lukman; Hendrawan, Andre Budhi; Zidni, Hepatika; Yohana, Eflita; Saptaryani, Titiek Deasy (Universitas Lancang Kuning, 2025)
Vocational High School (SMK) graduates are the biggest contributor to the unemployment rate. The Tegal Indonesia Bintang Manufaktur Job Training Institute helps increase the knowledge and skills of participants who incidentally are class XII SMK. Class XII who graduate in 2023 will certainly have low knowledge and competence because of the learning method used online (Covid-19 pandemic policy). The community service program (PKM) aims to strengthen basic competence, especially measuring. The method used is Training which is held for three days (20-22 March 2023). The results of PKM presented increase in measuring competency of 95.38% from 32 participants. Through the free test conducted at the beginning and the Post test at the end of the activity, measuring competence has been optimal as reflected in the practical implementation of Quality control